2019
DOI: 10.1055/s-0039-3400955
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Conversion to Five-Strand Hamstring Autograft Configuration Significantly Increases Anterior Cruciate Ligament Graft Diameter Independent of Patient Characteristics

Abstract: Intraoperative conversion of a four-strand hamstring autograft to a five-strand configuration during an anterior cruciate ligament (ACL) reconstruction has been reported. However, the expected change in graft size and the dependence on patient characteristics are currently not well described. The purpose of this study was to determine the effective change in hamstring graft diameter and reliance on patient characteristics when intraoperatively converting a four-strand hamstring autograft into a five-strand con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Hamstrings might also be transected prematurely during graft harvest. Facing a smaller-than-anticipated graft, the surgeon has 2 options: increase the number of graft strands by folding the graft more 11,17,26 or augment the graft with an allograft; however, both options have disadvantages. Increasing graft strands is not always feasible while retaining adequate graft length for bony integration, and allograft augmentation is still associated with a greater risk of rerupture, even though it yields a larger graft.…”
Section: Discussionmentioning
confidence: 99%
“…Hamstrings might also be transected prematurely during graft harvest. Facing a smaller-than-anticipated graft, the surgeon has 2 options: increase the number of graft strands by folding the graft more 11,17,26 or augment the graft with an allograft; however, both options have disadvantages. Increasing graft strands is not always feasible while retaining adequate graft length for bony integration, and allograft augmentation is still associated with a greater risk of rerupture, even though it yields a larger graft.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from Singapore [10] concluded that the 5-strand HT graft provided a signiicantly larger diameter compared with the 4-strand HT graft and that graft sizes exceeding 8 mm are achievable in 75% of patients with the routine application of this technique. Authors from United States [25] concluded that 5-strand HT autografts reliably increased intraoperative HT autograft diameter, by an average of 1 mm, compared with traditional 4-strand coniguration. The results suggest that a traditional 4-strand HT coniguration was usually inadequate to get a graft diameter greater than 8 mm in our male study population, resorting to 5-and 6-strand constructs to achieve appropriate graft size.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they had a contraindication to an FNB, allergy to the protocol medications, nervous system disease, renal or hepatic impairment, history of opioid dependence or current opioid use, or diagnosed psychiatric disease, were pregnant or lactating, or had a seizure disorder, history of postoperative nausea and vomiting, latex allergy, diagnosed cardiac or pulmonary disease, and/or body mass index of ≥40 kg/m 2 . A total of 3 board-certified, fellowship-trained sports medicine orthopaedic surgeons performed all of the H-ACLR surgeries using the technique described by Walczak et al 12 . This manuscript adheres to the applicable CONSORT (Consolidated Standards of Reporting Trials) guidelines.…”
Section: Methodsmentioning
confidence: 99%